Division-Free Multiquantization Scheme for Modern Video Codecs - Mousumi Das; Atahar Mostafa; Khan Wahid (Advances in Multimedia)
The current trend of digital convergence leads to the need of the video encoder/decoder (codec) that should support multiple video standards on a single platform as it is expensive to use dedicated video codec chip for each standard. The paper presents a high performance circuit shared architecture that can perform the quantization of five popular video codecs such as H.264/AVC, AVS, VC-1, MPEG-2/4, and JPEG. The proposed quantizer architecture is completely division-free as the division operation is replaced by shift and addition operations for all the standards. The design is implemented on FPGA and later synthesized in CMOS 0.18 μm technology. The results show that the proposed design satisfies the requirement of all five codecs with a maximum decoding capability of 60 fps at 187 MHz on Xilinx FPGA platform for 1080 p HD video.